Fringe Banking and Financialisation: Pawnbroking in pre-famine and famine Ireland - Eoin McLaughlin; Rowena Pecchenino (European Historical Economics Society (EHES), 2021)
Pawnbroking, one of the oldest and most accessible forms of credit, was a common feature of life in pre-famine and famine Ireland. This paper studies the role of pawnbroking in the Irish financial system during this important period, applying insights from modern studies on fringe banking to analyse pawnbroking in Ireland. In the period under study, a formal tiered financial system existed; regulated joint stock banks offered services to industry and the better off, while fringe banks provided financial services largely, but not exclusively, to unbanked groups. The main findings are that pawnbrokers provided a steady source of credit throughout the island of Ireland and that this credit stream was more durable than that provided by alternative financial service providers in the fringe banking market, especially during the famine. Our findings suggest a nuanced interpretation is needed as we find strong interrelationships between the various financial service providers.
Keywords: G21; G51; N23; 330; Fringe banking; financialisation; pawnbroking; Ireland